2019
DOI: 10.3390/jcm8111787
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adjustment of Endotracheal Tube Cuff Pressure during Scarless Remote Access Endoscopic and Robotic Thyroidectomy on Laryngo-Pharyngeal Complications: Prospective Randomized and Controlled Trial

Abstract: Scarless remote access endoscopic and robotic thyroidectomy has been recently performed as a safe and feasible method. However, little is known about the laryngo-pharyngeal complications after surgery and the effect of adjusting the endotracheal tube cuff pressure during surgery on laryngo-pharyngeal complications. Patients were randomized into two groups: the control group (n = 52) and adjusted group (n = 52). The initial cuff pressure was set to 25 mmHg and then monitored without adjustment (control group) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…We found that intubation resulted in a longer time until effective esophageal emptying was achieved. In our opinion, the cuff pressure of the endotracheal tube may affect upper esophageal motility [ 40 , 41 ], although the cuff pressure did not exceed 30 H 2 O in any of our patients. The upper and lower portions of the esophagus influence each other [ 1 ].…”
Section: Discussionmentioning
confidence: 68%
“…We found that intubation resulted in a longer time until effective esophageal emptying was achieved. In our opinion, the cuff pressure of the endotracheal tube may affect upper esophageal motility [ 40 , 41 ], although the cuff pressure did not exceed 30 H 2 O in any of our patients. The upper and lower portions of the esophagus influence each other [ 1 ].…”
Section: Discussionmentioning
confidence: 68%
“…Similarly, Inada et al showed that low endotracheal cuff pressure during hypothermic cardiopulmonary bypass was associated with low rates of tracheal mucosal ischemia 23 . On the other hand, Koo et al 24 reported that post-surgical sore throat rates were lower with lesser cuff pressures, while no such differences in the incidence of hoarseness or dysphagia were found by altering the cuff pressure during endoscopic and robotic thyroidectomy. Although no standardization of endotracheal cuff pressure measurements has been achieved yet, routine monitoring of cuff pressure is essential in preventing potential post-surgical complications 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative hoarseness (PH), defined as a harsh or strained voice characterized by an altered vocal quality [ 20 ], was assessed during the PACU stay and on PODs 1 and 2 using a scale of 0–3 (0 = none; 1 = mild, noticed by the patient only; 2 = severe, evident to the observer; 3 = aphonia, loss of voice) [ 19 ]. The incidence of PH was defined as the number of patients with a grade of hoarseness ≥ 1.…”
Section: Methodsmentioning
confidence: 99%